Germination biology, distribution and control of the invasive species Eragrostis curvula [Schard. Nees] (African Lovegrass): A global synthesis of current and future management challenges. (31st March 2021) - Roberts, Jason; Florentine, Singarayer; van Etten, Eddie; Turville, Christopher
Abstract: Eragrostis curvula (African Lovegrass) is an invasive C4 perennial grass that is threatening natural ecosystems globally. Native to Africa, this species can tolerate a wide range of environmental conditions, from acidic soils to areas with low rainfall and regions with frequent fires, which assists in its widespread distribution. With its large production of small seeds (0.3 to 0.7 mm) and quick seed germination, it has the ability to form dense swards which can limit the recruitment of other more desirable species in the landscape. Due to its invasive behaviour, E. curvula can now be found in several countries (Australia, Japan, New Zealand and the United States of America) where it causes environmental and economic degradation of the land, particularly if appropriate management is not applied. Previous management on the species has been focused on restoring competitive grasslands and pastures, grazing management, herbicide application, large‐scale burning and manual removal; however, in many regions there has been little to no long‐term success in reducing the species spread. Therefore, this review aimed to synthesise the existing research into the biology, distribution and management of E. curvula, whilst identifying any research gaps which may help improve the effective management of the species.